Coordination Chemistry of Uranyl Ions with Surface-Immobilized Peptides: An XPS Study - Esha Mishra; Cody M. Schultz; Rebecca Y. Lai; Peter A. Dowben (Molecules, 2022)
The coordination chemistry of uranyl ions with surface immobilized peptides was studied using X-ray photoemission spectroscopy (XPS). All the peptides in the study were modified using a six-carbon alkanethiol as a linker on a gold substrate with methylene blue as the redox label. The X-ray photoemission spectra reveal that each modified peptide interacts differently with the uranyl ion. For all the modified peptides, the XPS spectra were taken in both the absence and presence of the uranium, and their comparison reveals that the interaction depends on the chemical group present in the peptides. The XPS results show that, among all the modified peptides in the current study, the (arginine)9 (R9) modified peptide showed the largest response to uranium. In the order of response to uranium, the second largest response was shown by the modified (arginine)6 (R6) peptide followed by the modified (lysine)6 (K6) peptide. Other modified peptides, (alanine)6 (A6), (glutamic acid)6 (E6) and (serine)6 (S6), did not show any response to uranium.